Analisis Yuridis Tindak Pidana Korupsi Suap Berdasarkan Teori Kepastian Hukum - Azzahra, Syifa Nadya; Saragih, Yasmirah Mandasarih; Yusuf, Marzuki; Pasaribu, Ummi Rachmi (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
This study aims to analyze the criminal act of bribery corruption based on the theory of legal certainty. This research employs normative legal methods with statutory and conceptual approaches. The main focus is to examine the extent to which the principle of legal certainty is applied in court decisions related to bribery cases, particularly regarding the consistency of norm application and judicial considerations. It is found that in several similar cases, there are significant disparities in verdicts, both in terms of sentence length, fines, and additional penalties, without clear and uniform legal basis. This reflects the weak implementation of the principle of legal certainty as stated by Gustav Radbruch. Therefore, a revision of regulations and clearer, more standardized sentencing guidelines are needed to create clarity, predictability, and justice in law enforcement. The findings are expected to contribute academically to improving Indonesia’s criminal justice system, especially in handling corruption offenses